2008
DOI: 10.1002/ctpp.200810086
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Langmuir Probe Shaft on Measuring Plasma Parameters

Abstract: Because of their good spatial and temporal resolution Langmuir probes are often used for plasma diagnostics. One has to keep in mind, however, that the presence of the probe can substantially perturb the neighboring plasma. Apart from the probe tip, in particular the probe shaft may affect the measured values of temperature and density. We have studied this latter effect at the linear plasma generator PSI-2 which provides a stationary plasma column of 2.6 m in length and 8 cm in diameter. Two single probes dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The measured equilibrium electron density and temperature profiles are found to be in reasonable agreement with current and previous measurements by other plasma diagnostics [103,104,105,80,106]. It was found that the general assumption of an azimuthal symmetry in these profiles is not always given, and depends on the gas species and discharge conditions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The measured equilibrium electron density and temperature profiles are found to be in reasonable agreement with current and previous measurements by other plasma diagnostics [103,104,105,80,106]. It was found that the general assumption of an azimuthal symmetry in these profiles is not always given, and depends on the gas species and discharge conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Generally, Langmuir probes were found to change the PSI-2 plasma globally when measuring profiles with two probes at the same time. The probe acts as an additional sink, reducing the density considerably, while temperatures remained unchanged [104]. Fast camera measurements confirmed changing plasma emissions and their oscillation frequency during the probe measurements.…”
Section: Discussionmentioning
confidence: 69%
“…Usually electrostatic probes are used to infer n e . However, it is widely known that electrical disturbances and perturbances due to the presence of the macroscopic probe holder can distort the results [1][2][3][4]. It is obvious that alternative non-intrusive diagnostics are needed additionally.…”
Section: Introductionmentioning
confidence: 99%